Water activated skin adhesives - Liu, Zong Yao (Nanyang Technological University, 2024)
Bioadhesives have been gaining popularity as a result of the increased demand of management of wound closure and haemostasis, providing a minimally invasive wound closure method that can achieve scarless wound healing, unlike other conventional methods such as sutures or staples. However, bioadhesives have potential cytotoxicity and require further development on their adhesive strength, limiting its uses in clinical applications.